Estetika Teknik Slashing pada Produk Tote Bag - Desneysha Muji Nugraheni; Vivi Radiona; E. Lutfia Zahra (Universitas Negeri Surabaya, 2025)
This study aims to obtain aesthetic data on five tote bag products with slashing technique decoration applications which include three aspects of assessment, namely the form or form aspect which includes the application of design elements and design principles, the weight or content aspect which includes the delivery of ideas or ideas, and the appearance or presentation aspect which includes the application of means or media. The research method uses quantitative with a pre-experimental design of one shot case study type. The data collection technique used a mixed questionnaire. The instrument in this study consisted of 18 statements with a rating scale measurement scale distributed to 5 expert panelists in their fields. The results of the research on the aesthetics of slashing techniques on tote bag products obtained an overall score of 91.4 which is included in the very good category. The aesthetic aspect that gets the highest score is the appearance or presentation aspect with a score of 93.3 which is included in the very good category. While the product that received the highest score was product 2 with a score of 92.2% which is included in the very good category. This shows that the aesthetic aspects of form or appearance, weight or content, and appearance or presentation in accordance with A.A.M Djelantik's aesthetic theory are very good in their application to tote bag products with slashing techniques.